PENGGUNAAN MODEL TPS UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS IV SD - Tinambunan, Risda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem in this research is whether by using think-pair-share model in science learning can improve student learning outcomes in grade class Public Elementary School 30 South Pontianak . This study aims is to improve student learning outcomes in natural science learning. This research is the form of Classroom Action research and using descriptive and collaborative method. Place of this research took place in grade class State Elementary School 30 South Pontianak. The subjects of this study are teachers and 20 students of grade class State Elementary School 30 South Pontianak. Data collection techniques used are direct observation techniques with data collection tools that is IPKG 1 and IPKG 2 in the implementation of learning, and documents student learning outcomes. This research lasted for 3 cycles of research result on teacher ability to plan study the first sycless got score 3,26 insecond cycle to 3,66 in third cycle become 3,89 ability of teacher in doing learning on first cycle get score 3,31 at second cycle got a score of 3.56 and in third cycle got a score of 3.91. Student learning outcomes in first cycle is 66 then in second cycle average student learning outcomes is 78.4 and on the implementation of third cycle average learning outcome is 91. Based on all observational data in the three research cycles on the use of tps model in natural science learning to improve the learning outcomes of fourth graders Public Elementary School 30 South Pontianak the data shows an increase from first cycle to third cycle. Thus the think pair share model can improve student learning outcomes in class IV State Elementary School 30 South Pontianak. Keywords: Usage, Think Pair Share, Learning Outcomes, Natural Science